Estimated stearoyl-CoA desaturase activity mediates the associations of total cysteine with adiposity: The Maastricht Study - Tore, Elena C; Adriaans, Bregje C; Olsen, Thomas; Vinknes, Kathrine J; Kooi, M Eline; Elshorbagy, Amany K; Bastani, Nasser E; Dagnelie, Pieter C; Eussen, Simone J P M; Gundersen, Thomas E; Kožich, Viktor; Refsum, Helga; et al. (Journal of clinical lipidology, 2025)
BACKGROUND: Plasma sulfur amino acids (SAAs), particularly cysteine, are associated with obesity. One proposed mechanism is the altered regulation of the stearoyl-CoA desaturase (SCD) enzyme. Changes in the SCD enzyme activity have been linked to obesity, as well as to plasma SAA concentrations. OBJECTIVE: This study aimed to investigate whether estimated SCD activity mediates the associations between plasma SAAs and measures of overall adiposity and specific fat depots. METHODS: We examined cross-sectional data from a subset of the Maastricht Study (n = 1129, 50.7% men, 56.7% with (pre)diabetes). Concentrations of methionine, total homocysteine, cystathionine, total cysteine (tCys), total glutathione (tGSH), and taurine were measured in fasting plasma. Outcomes included measures of overall, peripheral and central adiposity, and liver fat. SCD activity was estimated by ratios of serum fatty acids as SCD16 and SCD18 indices. The associations between plasma SAAs and measures of adiposity or liver fat were examined with multiple linear regression analysis. Multiple mediation analysis was used to investigate whether the significant associations were mediated by SCD16 and SCD18 indices. RESULTS: Plasma tCys was positively associated with all adiposity measures (β ranged from 0.15 to 0.30). SCD16 significantly mediated all associations (proportion mediated ranged from 5.1% to 9.7%). Inconsistent mediation effects were found for SCD18. Despite a significant inverse association of plasma tGSH with all adiposity measures (β ranged from -0.08 to -0.16), no significant mediation effect was found. CONCLUSIONS: Plasma tCys may promote excessive body fat accumulation via upregulation of SCD activity.
Keywords: dospělí; cystein; Female; Adult; ženské pohlaví; průřezové studie; Obesity; lidé; stearyl-CoA-desaturasa; Adiposity; Stearoyl-CoA desaturase; adipozita; Plasma sulfur amino acids; Body fat depots; Stearoyl-CoA Desaturase; Cross-Sectional Studies; obezita; Male; Cysteine; Total cysteine; lidé středního věku; mužské pohlaví; Middle Aged; Humans